Contribution of feed supplementation to zootechnic performance of African dwarf sheep in West Africa: A review - Dokui, Faustin; Chrysostome, Christophe A.A.M.; Babatoude, Severin; Houndonougbo, Frederic M. (Syiah Kuala University, 2023)
Like gasoline is essential for a combustion engine,feed is indispensable for animals. Besides the main feed, a supplemental diet is essential, even indispensable, to help animals reach optimal production in the ruminant feeding and nutrition system. The main objective of this review was to summarize the research performed across the West Africa area on diet supplementation for African dwarf sheep. By examining some scientific articles published from 2010 to 2021, identified mainly from Scilit, Google Scholar, Elsevier, Springer Nature, PubMed, AJOL, and Scirp, we identified more than 43 feed supplements made from more than 96 local ingredients grouped into 54 agricultural and industrial by-products, seven minerals and vitamins, four fodders, and four binders and other ingredients such as enzymes. The nutritional content of most of those feed supplements based on their crude protein, crude fiber, ash, calcium, phosphorus, and gross energy contents meet recommended standards of NRC. The digestibility of the nutritional component of the feed supplement fluctuates from 20.90% (organic matter) to 94.85% (ether extract). They enabled a good average daily gain (37.03 g to 100 ga good feed conversion ratio (4.62 to 13.73). The review shows that it is possible to achieve acceptable zootechnical performance using feed supplements made with local ingredients available in each West African country.